Regulatory scientists’ work has important ramifications for public health and should be open to public scrutiny - Mulinari, Shai (Health Res Policy Syst, 2018)
The Swedish Medical Products Agency (MPA) objects to the fact that we occasionally refer to one of its senior ex-employees by name. However, names of individual MPA assessors, Food and Drug Administration (FDA) reviewers, and European Medicines Agency rapporteurs and co-rapporteurs are cited in regulatory documents and are a matter of public record. In our paper (Health Res Policy Syst 15:93, 2017), we in no way suggest that regulatory decisions were left to individual reviewers or assessors, although we do emphasise that individual MPA and FDA employees’ scientific assessments and benefit–risk evaluations are critical to the decision-making process. In this response to the MPA, we raise a further issue – one in which the question of personal identification of individuals is relevant – and this pertains to the accountability of influential scientists and experts who contribute to public policy decisions with important ramifications for public health. In our view, it is important that interested observers are able to identify those influential individuals, and entirely appropriate that their work should be open to public scrutiny.